Regulating Utilities - World Bank (Washington, DC, 2012)
Regulating infrastructure utilities can be extremely complex and fraught with risks of political interference and capture by interest groups, especially in countries with little tradition of politically independent government agencies. To deal with these challenges, policymakers and regulators have sometimes contracted third parties-such as independent experts and consultants-to provide advisory or binding input into the administration of regulatory functions. This Note examines international experience in this area and explores the key implications for policymakers.